Assessment of Visual and Brainstem Auditory Evoked Potentials in Patients with Hashimoto’s Thyroiditis - Marta Waliszewska-Prosół; Maria Ejma (Journal of Immunology Research)
Background. The present study was aimed to evaluate parameters of visual and brainstem auditory evoked potentials (VEP, BAEP) in euthyreotic Hashimoto’s thyroiditis (HT) patients without central nervous system involvement. Methods. 100 HT patients (92 women, 8 men), mean age 46.9 years, and 50 healthy controls. They underwent a neurological examination, thyroid hormone levels, thyroid autoantibody titers, and brain imaging. Latencies and amplitudes of the N75, P100, and N145 component of VEP and the I-V components of BAEP were analyzed. Results. The neurological examination revealed in 31 patients signs of increased neurovegetative excitability. Brain resonance imaging showed no abnormalities in HT patients. The mean P100, relative P100, and N145 VEP latencies were significantly longer, and P100 amplitude significantly higher in HT patients than the controls. HT patients also had a longer mean wave BAEP V latency and mean wave III-V and I-V interpeak latencies, and significantly lower mean wave I and V amplitudes. Abnormal VEP and BAEP were recorded in 34% of the patients. There were no statistically significant correlations between the mean VEP parameters and thyroid profile and the applied dose of L-thyroxine. There was a relationship between the level of TSH and the wave BAEP III-V interpeak latency. Conclusions. There were changes in the brain’s bioelectrical activity in one-third of the patients with HT without nervous system involvement. The increased amplitude of the VEP may indicate increased cerebral cortex activity. Disorders of the brain’s bioelectrical activity in the course of HT may be associated with an autoimmune process.